(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Human beings are connected inextricably with nature that can influence our mental and physical well-being. People nowadays working in the hustle and bustle city has a low connection with nature, resulted in humankind suffering from mental illness. Connection to nature is essential for human beings to keep a healthy mind. This study mainly concentrates on the impact of blue space in the interior on mental health. In this research, previous studies are analyzed to understand the theory behind the blue space on how water benefits humans. Moreover, the researcher identifies thirty pieces of literature about water and health. The literature review is categorized into sensual perception (visual, sound, or music and sense of water) and the impact of blue space (emotional benefits, stress relief, direct health benefits) to reveal the idea of how the blue space benefits people. This paper is carried out through qualitative methods. Research shows intervention evidence of the visuals, sounds, and sense of water impact our health in the interior. The findings indicate the function of blue space in the interior on mental health. These findings help in a better understanding of the impact of water sounds in the interior on mental health.